(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Nagapattinam, in the east coast of India, was severely affected during the deadliest Indian Ocean tsunami of December 26, 2004. The tsunami caused heavy damage to life and property, and the death toll was about 3,378 in Nagapattinam Taluks. Certain villages along the coast witnessed large inundation while adjacent villages were protected from the fury of the tsunami waves. This study was carried out to examine the underlying causes for the vulnerability along Nagapattinam coast with the help of field observations, remote sensing, and geographical information system as tools. This area is one of the vulnerable sites affected by Tsunami on 26th December 2004, which caused great damages. India has a long coastline of about 7500 km including its island territories. Ports handle about 95% of India’s foreign trade by weight/volume through maritime transports. Harbour environment can be divided into four components –sea surface, shoreline, ocean, floor, and the body of the ocean composed of water columns and suspended sediments. Ports and Harbour create local environmental problems Nagapattinam port is one of the minor port among 212 ports in India. In this present study shoreline changes and the sediment dynamics were analyzed using topo sheets, beach slope measurement and sample characteristics. The sediment transport directions during monsoon and post monsoon seasons were found. The results were compared with variation of monsoon.